Effect of age on exercise-induced bronchoconstriction in children and adolescents with asthma. (1st February 2022) - Motomura, Chikako; Matsuzaki, Hiroshi; Odajima, Hiroshi; Oki, Takeshi; Yasunari, Yusuke; Kawano, Toshiaki; Iwata, Mihoko; Okabe, Koki; Wakatsuki, Masatoshi; Murakami, Yoko; Taba, Naohiko; Honjo, Satoshi; et al.
Abstract: Objective: The relationship between exercise-induced bronchoconstriction (EIB) and exertional dyspnea in children and adolescents is yet to be fully established. This study examined whether indicators of fractional exhaled nitric oxide (FeNO), forced expiratory volume in 1 s (FEV1 ) percent predicted at baseline, and dyspnea are useful for predicting children and adolescents with EIB. Methods: We enrolled 184 children and adolescents diagnosed with asthma (mean age 11.2 years); participants were divided into two groups according to age (12 years) and were subjected to a 6-min exercise challenge test. Lung function tests and modified Borg scale scores were used to examine perceptions of dyspnea at 0, 5 and 15 min after exercise. Results: Among children, the maximum percentage drop in FEV1 after exercise correlated significantly with FeNO (adjusted β = 2.3, P < 0.001) and with the perception of dyspnea at 5 min after exercise (adjusted β = 1.9, P < 0.001). Among adolescents, the maximum percentage drop in FEV1 correlated with FeNO (adjusted β = 2.7, P = 0.007) and with lung function (FEV1, percent predicted; adjusted β = −0.28, P = 0.006). Children with EIB had significantly stronger dyspnea after exercise than did children without EIB. Adolescents even without EIB may experience more exertional dyspnea than children without EIB. Conclusions: Overall, our findings indicated that EIB was associated with FeNO and exertional dyspnea in asthmatic children. By contrast, EIB was associated with FEV1 percent predicted at baseline and FeNO but not with exertional dyspnea in asthmatic adolescents.